Type D Retrovirus Capsid Assembly and Release Are Active Events Requiring ATP - Weldon, Robert A. (American Society for Microbiology, 1998)
Mason-Pfizer monkey virus (M-PMV), the prototype type D retrovirus, differs from most other retroviruses by assembling its Gag polyproteins into procapsids in the cytoplasm of infected cells. Once assembled, the procapsids migrate to the plasma membrane, where they acquire their envelope during budding. Because the processes of M-PMV protein transport, procapsid assembly, and budding are temporally and spatially unlinked, we have been able to determine whether cellular proteins play an active role during the different stages of procapsid morphogenesis. We report here that at least two stages of morphogenesis require ATP. Both procapsid assembly and procapsid transport to the plasma membrane were reversibly blocked by treating infected cells with sodium azide and 2-deoxy-d-glucose, which we show rapidly and reversibly depletes cellular ATP pools. Assembly of procapsids in vitro in a cell-free translation/assembly system was inhibited by the addition of nonhydrolyzable ATP analogs, suggesting that ATP hydrolysis and not just ATP binding is required. Since retrovirus Gag polyproteins do not bind or hydrolyze ATP, these results demonstrate that cellular components must play an active role during retrovirus morphogenesis.